THE EFFECTIVENESS OF USING MULTIMEDIA MATERIALS IN TEACHING CULTURE TO EFL LEARNERS - Danabaeva, Khurshida (MMIT Proceedings, 2023)
The qualification paper is dedicated to teaching culture through multimedia tools to EFL learners. Therefore, it tends to analyze the methods of teaching culture in initial stages and determine the more efficient ones. The core purpose of this thesis is to suggest more appropriate ways of teaching culture so the seventh-grade pupils assimilate the language easily, without any troubles. The theory was proving that the researcher used multimedia tools in teaching learners to learn language and culture.